A Quantitative Analysis of Stock Price in The Indonesian Industrial Sector - Venice, Gracea; Cahyani, Natasya; Marpaung, Sandy Estrina Claudya; Ramadani, Arienda Gitty (MDP Student Conference, 2024)
This research examines the impact of Return on Equity (X1), Net Profit Margin (X2), Debt to Equity Ratio (X3), and Price Earnings Ratio (X4) on stock prices (Y). Research was conducted on industrial companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique used was purposive sampling and there were 33 out of 63 industrial companies that met the criteria. Research analysis uses IBM SPSS 27 software for multiple linear regression analysis. The analytical methods used are the classic assumption test which includes the normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test, and the suitability model through the F test and coefficient of determination test, and hypothesis testing through the T test. The research proves X1 and X2 variables have a significant effect on stock prices, while X3 and X4 variables do not. These findings offer valuable insights for investors in evaluating industrial sector performance.